Shear capacity of singly and doubly webbed corrugated web girder / Hanizah Abdul Hamid, Azmi Ibrahim and Norhisham Ibrahim - Abdul Hamid, Hanizah; Ibrahim, Azmi; Ibrahim, Norhisham (Institute of Research, Development and Commercialisation (IRDC), 2006)
A conventional plate girder involves the use of transverse intermediate stiffeners, especially in a slender web to avoid catastrophic failure associated with shear buckling of the web. In this study, a profiled web was used to replace the transversely stiffened web. The process involves introducing coldformed ribs into a flat steel sheet to form alternative stiffeners. This study therefore seeks to establish comparative performance of conventionally stiffened plate girders and profiled web girders of a specially formed rib arrangement with single and also double webs. Nine numbers of specimens were tested to failure under a three-point-bending system. Failure of all the profiled web girders, with either a single or double webs, is characterized by a shorter yield plateau and a steeper descending branch, a failure mode that is commonly referred to as ‘brittle’. The results of the tests on girders with profiled steel sheets, PSS(s) have shown that profiling is extremely effective in increasing the shear buckling load because it moves the sheet material out of the plane of the web, thereby increasing the rigidity 1.08 to 2.0 times higher than the equivalent conventional flat web plate girders. The experimental results also showed that post-buckling capacities are reduced by 30 % to 50 % of their ultimate shear capacities.